Clinicopathological Characteristics, Treatment, and Prognosis of 21 Patients with Primary Gastric Squamous Cell Carcinoma - Yang Chen; Hong Zhu; Feng Xu; Yidan Cao; Xingting Gu; Yuming Wan; Hongfeng Gou (Gastroenterology Research and Practice)
We performed a retrospective analysis of 21 patients with primary gastric squamous cell carcinoma (PGSCC) who were admitted to our hospital from October 2008 to October 2014. The median age was 67 years and male predominance was observed, the most common tumor locations were the upper third of the stomach, most of the clinical manifestations were identical to those of other types of gastric tumors, and the tumor cells had positive immunoreactivity for p63 and CK5/6. In terms of treatments, surgery (R0 resection) is the main treatment; the effect of other treatments is unclear. The median survival time for the surgery group and nonsurgery group was 46 and 4.5 months, respectively. Probably due to limited number of cases, no significant difference in median survival time was observed between the surgery alone group and the surgery plus adjuvant therapy group (46 versus 51 months, P=0.310). A standard chemotherapy regimen for this disease has not yet been established; the choice of its chemotherapy regimens tends to follow the principle of the treatment of gastric adenocarcinoma or esophageal cancer. PGSCC generally had a poor prognosis, and early detection, early diagnosis, and early surgical treatment are beneficial to patients.